Studies on wound healing - Fenton, H. (1963)
Factors affecting the rate of healing of experimental skin wounds in rats have been investigated. The effectiveness of healing was measured by determining the tensile strengths of the incised skin after various time intervals. When the skin histamine content was lowered by treatment with polymyxin B or with compound 48/80, retardation of the healing process was evident from the reduced tensile strengths. When the skin 5-hydroxytryptamine content was lowered by treatment with reserpine, retardation of healing was also found. Heparin increased the rate of healing and more rapid healing was obtained by giving histamine before each dose of heparin. On the other hand, some glucocorticoids markedly inhibited the healing process. Of the constituents of the tissue mast cells, heparin appears to be more important than histamine and 5-hydroxytryptamine in promoting the healing of experimental skin wounds in rats.